2019
DOI: 10.1038/s41556-019-0347-9
|View full text |Cite|
|
Sign up to set email alerts
|

ATF4 couples MYC-dependent translational activity to bioenergetic demands during tumour progression

Abstract: The c-Myc oncogene (MYC) drives malignant progression, but also induces robust anabolic and proliferative programs leading to intrinsic stress. The mechanisms enabling adaptation to MYC-induced stress are not fully understood. We have uncovered an essential role for the transcription factor ATF4 in survival following MYC activation. MYC upregulates ATF4 by activating GCN2 kinase through uncharged tRNAs. Subsequently, ATF4 co-occupies promoter regions of over 30 MYC target genes, primarily those regulating amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
161
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 59 publications
14
161
2
Order By: Relevance
“…upregulated glycolytic and downregulated TCA cycle activity leading to consequent reduction in inflammatory cytokine production and anergy- are best explained by the observed H3K27 mediated silencing of key transcription factors such as MYC, PPARg and PPRC1 as a consequence of GSK-J4 treatment (61). Recently, it has been shown that inhibition of mTORC1 signalling rescues ATF4-deficient cells from MYC-induced endoplasmic reticulum stress (60). This reveals an essential role for ATF4 in survival following MYC activation and our data suggests that KDM demethylases are an important regulator of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…upregulated glycolytic and downregulated TCA cycle activity leading to consequent reduction in inflammatory cytokine production and anergy- are best explained by the observed H3K27 mediated silencing of key transcription factors such as MYC, PPARg and PPRC1 as a consequence of GSK-J4 treatment (61). Recently, it has been shown that inhibition of mTORC1 signalling rescues ATF4-deficient cells from MYC-induced endoplasmic reticulum stress (60). This reveals an essential role for ATF4 in survival following MYC activation and our data suggests that KDM demethylases are an important regulator of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this methionine--dependent context, cells co-opt Gcn4, which is conventionally viewed as a 'survival/stress' transcription factor, to provide this supply of metabolic precursors. Relevantly, recent studies of the mammalian ortholog of Gcn4 (ATF4) now report high ATF4 activity in several cancers (Pällmann et al, 2019;Singleton and Harris, 2012;Tameire et al, 2019;Ye et al, 2010). These studies suggest that ATF4 induction is critical for tumor progression during nutrient limitation, possibly by providing otherwise limiting metabolites (Tameire et al, 2019;Ye et al, 2010).…”
Section: Gcn4 Dependent Lysine and Arginine Supply Is Essential To Mamentioning
confidence: 95%
“…Relevantly, recent studies of the mammalian ortholog of Gcn4 (ATF4) now report high ATF4 activity in several cancers (Pällmann et al, 2019;Singleton and Harris, 2012;Tameire et al, 2019;Ye et al, 2010). These studies suggest that ATF4 induction is critical for tumor progression during nutrient limitation, possibly by providing otherwise limiting metabolites (Tameire et al, 2019;Ye et al, 2010). Separately, observations over decades note that many tumors depend on sulfur amino acids, especially methionine (Breillout et al, 1990;Poirson--Bichat et al, 2000), and methionine restriction critically determines tumor progression (Gao et al, 2019b(Gao et al, , 2019a.…”
Section: Gcn4 Dependent Lysine and Arginine Supply Is Essential To Mamentioning
confidence: 99%
“…Although it is primarily studied in the context of starvation, during a methionine driven growth program Gcn4 activity fuels the synthesis of required biosynthetic precursors to drive growth. Interestingly, such scenarios are also observed in several tumors, where the mammalian ortholog of Gcn4 (ATF4) is induced and helps in tumor proliferation (57)(58)(59)(60). The mechanisms of induction of ATF4 in these contexts have not been well studied, and the mechanism observed in this study is plausible in those contexts of high growth.…”
Section: Discussionmentioning
confidence: 63%